Representação social de adolescentes sobre o "viciado" em drogas - Cuvello, Sulamita Táita Vitorino (2004)
The research discusses the social representation elaborated by the adolescents about thee drug "addict", expressing how the use of psychoactive substances evolved since the "primitive" societies until contemporary society. We attempted also to verify the main motives that influence drug consumption at this age, according to the subjects, identifying the forms of prevention performed by the school. We highlight also some factors that can be construed as predisposing to drug use during the adolescence. The study was based in a psychosocial approach, conceptually and methodologically oriented by the theory of social representations, based upon the central core theory. Participated 140 students, 70 from public schools and 70 from the private sector, with ages varying from 15 to 20 years, who answered a collectively applied script. The data were analyzed with the aid of the software EVOC, in the question of free association that used the inductor term, "drug addict", and the software ALCESTE for content analysis on the remaining questions. The results indicated, both on public school and on private school, the existence of a common field of social representations structured around the conception of "addict" as an unfortunate person, inspiring feelings of pity and of someone who needs help. The study reveals also that the adolescents of private school emphasize more than their counterparts on public school that the "addict" is the main responsible for the addiction.